An exploratory study of clinicians' perceptions and experiences of the phenomenon of 'sex addiction' in South Africa - Abel_R (Department of Social Development, 2024)
The naming of compulsive sexuality as sex addiction is recent and is a relatively new and emerging field abroad. While research in this field has proliferated in the United States since the 1980s, South African studies are limited. This study explores how mental health practitioners perceive and treat the phenomenon referred to popularly as sex addiction. Practitioners' perceptions and experiences in this field in Cape Town have not been explored and this thesis hopes to redress that. The research is empirical, qualitative and inductive in nature. Drawing primarily on psychodynamic theory, and to a lesser degree, applying a social constructionist perspective, it explores perceptions and experiences of practitioners working in this field. Practitioners were selected by a purposive and snowball sampling process and a semistructured interview schedule was administered to a sample of nine practitioners. The data was analysed using thematic analysis. Key conclusions drawn from the data include: as a concept, sex addiction remams contested and is utilised by only a small number of health professionals. The majority of mental health practitioners refutes its existence or prefers not to work with this phenomenon. Those working with the clinical problem insist that it has a circumscribed clinical picture with clearly identifiable criteria. It is seen to have an extremely complex aetiological base, requiring a variety of intervention models and techniques. Intervention is seen to be long-term, concerned with addressing fundamental developmental injuries, and is fraught with setbacks and resistance on the part of the clientele. At the same time, practitioners experience it as exciting and rewarding work. As part of the field of human sexuality, it is beset by society'S sexual taboos which makes for decreased disclosure and hampers effective intervention. While it is seen as primarily a male problem, it is acknowledged that sex taboos are more pronounced for women. Some respondents assume that women endure similar difficulties but have more prohibitions around disclosure than men do. Further research, skilled diagnostic procedures and increased knowledge among clinical professionals of the phenomenon and its impact on their clientele, are seen as important avenues through which practitioners can offer a more comprehensive service in this field.